PENGEMBANGAN LKPD DENGAN PENDEKATAN STEM BERBASIS E-LEARNING PADA MATERI BESARAN DAN SATUAN - Abdillah, Muhammad Taufiq; Wulandari, Dewi (Universitas Negeri Medan, 2023)
Designing relevant, effective, and valid student worksheet teaching materials is the goal of this project. by utilizing a STEM strategy focused on e-learning for magnitude and units. The ADDIE model and the R&D approach were used to conduct this study. Three validators are used to determine the product's validity during the creation stage: material experts, media experts, and teachers. A normalized gain test (N-Gain) was conducted to evaluate the product's efficacy. Moreover, depending on the feedback from the students, to assess the product's practically. There are small-scale tests with 10 students and large-scale tests with 20 students used in product development. The instruments employed were expert validity questionnaires and student response questionnaires. Testing for validity, efficacy, and practicality on goods reveals that the produced LKPD is highly valid, highly effective, and highly practical as a teaching resource in learning activities.